2021
DOI: 10.1128/spectrum.01283-21
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characterization of Group B Streptococcus Infections in Alberta, Canada: An Update from 2014 to 2020

Abstract: This work describes the epidemiology of invasive infections caused by the bacterium group B Streptococcus (GBS) in Alberta, Canada. We show that rates of invasive GBS disease have increased from 2014 to 2020 for both adult disease and late-onset disease in neonates, whereas the rate of early onset disease in neonates has decreased. We also show that the rate of resistance to erythromycin (an antibiotic used to treat GBS) has also increased in this time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…In this study, we characterized serotype VIII GBS isolates identified in Alberta from January 2003 to September 2021 [ 14 , 16 ]. The goal was to characterize this emerging group within Alberta primarily through genomic analyses, as there are no previous genome-based studies focused on this group to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, we characterized serotype VIII GBS isolates identified in Alberta from January 2003 to September 2021 [ 14 , 16 ]. The goal was to characterize this emerging group within Alberta primarily through genomic analyses, as there are no previous genome-based studies focused on this group to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, antimicrobial resistance was limited, with only one isolate exhibiting erythromycin and inducible clindamycin resistance (Table 1 ). Alberta has seen increases in resistance to erythromycin and clindamycin among invasive GBS, especially among adult isolates [ 14 ]. In a study comparing changes in resistance rates among GBS isolates in Alberta between 2003–2013 and 2014–2020, erythromycin non-susceptibility rose from 36.9 to 50.8% and clindamycin non-susceptibility rose from 21.0 to 45.8% between the two time periods [ 14 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations